ACTUALISATION OF ISLAMIC EDUCATION FOR CHILDREN IN FAMILY LIFE IN RANGAS NEIGHBOURHOOD, RANGAS VILLAGE, MAJENE REGENCY - Dzulhaj, Nurfajriyah; Malli, Rusli; Sumiati, Sumiati (Universitas Islam Negeri Alauddin Makassar, 2024)
Islamic education is the most important and important provision for children, and that's why parents have a responsibility to children in terms of providing teaching, especially Islamic religious education as a provision for children to welcome the future. Islamic religious education in the family environment should be well actualized because Islamic religious education is a strong initial foundation for children and families, especially parents have an important role in providing Islamic education to children, especially in today's modern era parents must pay extra attention to parenting and providing Islamic religious education. The obligation of parents to provide education to children is in line with the right of children to get education from their parents. This is explained in the 1945 Constitution in article 208 (1)